Refractory Thrombocytopenia in Antiphospholipid Syndrome: Case Report and Mini Literature Review - Aversano, Maria Gloria; Botta, Alice; Sbattella, Matteo; Balossi, Luca Giuseppe; Colombo, Fabrizio (Archives of Clinical and Medical Case Reports, 2022)
Antiphospholipid Syndrome (APS) is a condition characterized by clinical features of thrombosis and repeated miscarriages (criteria manifestations) accompanied by presence of antiphospholipid antibodies on laboratory tests. APS is a disease that can also present different clinical manifestations (non-criteria manifestations), including livedo reticularis, cutaneous ulcerations, thrombocytopenia, hemolytic anemia, valvular heart disease, and nephropathy, for which the gold standard treatment is often not known. Most of the APS management guidelines focus on the prevention and treatment of thrombotic and obstetrical manifestations, by anticoagulant therapy. However there is less consensus on the gold standard treatment for other clinical manifestations, which can have a serious impact on the health of the affected patient. Here we present a case report that emphasizes the importance of identifying correct therapy for non-criteria clinical manifestations of APS triggered by post-traumatic left fronto-temporal hematoma, subsequent neurosurgical intervention complicated by subdural empyema.